2011
DOI: 10.1002/hbm.21084
|View full text |Cite
|
Sign up to set email alerts
|

The impact of iconic gestures on foreign language word learning and its neural substrate

Abstract: Vocabulary acquisition represents a major challenge in foreign language learning. Research has demonstrated that gestures accompanying speech have an impact on memory for verbal information in the speakers' mother tongue and, as recently shown, also in foreign language learning. However, the neural basis of this effect remains unclear. In a within-subjects design, we compared learning of novel words coupled with iconic and meaningless gestures. Iconic gestures helped learners to significantly better retain the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
191
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 233 publications
(212 citation statements)
references
References 117 publications
(105 reference statements)
14
191
2
5
Order By: Relevance
“…Cospeech gestures might activate a motor image that matches an underlying representation of the word's semantics (Macedonia, Mü ller, & Friederici, 2011). This in turn could lead to a deeper encoding because of multi-modal representation in memory (Feyereisen, 2006).…”
Section: Findings In Healthy Control Subjectsmentioning
confidence: 99%
“…Cospeech gestures might activate a motor image that matches an underlying representation of the word's semantics (Macedonia, Mü ller, & Friederici, 2011). This in turn could lead to a deeper encoding because of multi-modal representation in memory (Feyereisen, 2006).…”
Section: Findings In Healthy Control Subjectsmentioning
confidence: 99%
“…Focusing on two key elements of McNeill's theory-bi-directionality and obligatory integration-they presented evidence that gesture and speech mutually and automatically affect the semantic processing of one another during the comprehension process (for more on this relationship during comprehension, see Hostetter, 2011). This tight semantic relationship appears to extend beyond one's native language and apply to second languages (L2) and foreign languages (FL) as well (Gullberg;2006;Hardison, 2010;Kelly, McDevitt, & Esch, 2009;Macedonia, Müller, & Friederici, 2011;McCafferty & Stam, 2009;Quinn-Allen, 1995;Tellier, 2008). Focusing on FL comprehension, Kelly and colleagues (2009) showed that people learn and remember novel vocabulary items better when they are instructed with iconic hand gestures, and one neural mechanism responsible for this learning may be a strengthening of visual semantic representations.…”
mentioning
confidence: 99%
“…Firstly, enacting a word leaves a motor trace in one's memory [23]. This has been convincingly proven in neuroscientific experiments in which it is possible to detect activity in motor areas upon acoustic or visual word presentation [24,25]. Secondly, enhancement results from motor imagery [26,27]: it leads to deeper information processing [28] and has positive effects on memory.…”
Section: B the Methods: Enactmentmentioning
confidence: 93%